The benefit of platelet-rich plasma injection over institution-based physical therapy program in adhesive capsulitis patients with diabetes mellitus: prospective observational cohort study - Apurba Barman; Somnath Mukherjee; Mithilesh K Sinha; Jagannatha Sahoo; Amrutha Viswanath (Clinics in Shoulder and Elbow, 2021)
Background The objective of this study was to compare the efficacy of platelet-rich plasma (PRP) injection with an institution-based physical therapy (PT) program for adhesive capsulitis (AC) of the shoulder in patients with diabetes mellitus (DM). Methods A total of seventy diabetic patients with AC of the shoulder for <6 months were assigned to two groups: PRP group and PT group. In the PRP group, 35 patients were administered a single shot of PRP (4 mL) into the glenohumeral joint. In the PT group, 35 patients were given institution-based PT that included 10 30-minute sessions of planned PT over a 2-week period. After the interventions, all patients were prospectively followed for 12 weeks. Intensity of shoulder pain, function, and range of motion were assessed at baseline and then at 3, 6, and 12 weeks. Results Thirty-three patients in the PRP group and 32 in the PT group completed the 12-week study. At 12 weeks, patients who received PRP injections showed greater improvement in shoulder pain (p<0.001) than those recruited to the PT group. In the range of motion and shoulder function activities, patients in the PRP group showed significant improvement compared with the institution-based PT group (p<0.001). No significant complications were reported from any groups. Conclusions In a diabetic population, PRP injections significantly improved shoulder pain and function compared with an institution-based PT program for shoulder AC. Additionally, it is a safe and well-tolerated method for AC management for diabetic patients.